CPM 5. Duration of incubation and growing orientation of fruiting bags for milky mushroom (Calocybe indica P&C) (2018)
This research was conducted at Laguna State Polytechnic University, Siniloan Laguna to determine the growth and yield performance of milky mushroom with different duration of incubation and growing orientations of fruiting bags. The treatment were: duration of incubation of fruiting bag (2 months old, 4 months old), and growing orientations (upright,lying,sliced longitudinally, slice cross-sectionally, conventional method). Results shows that the growth characteristics (number of days) from casing application to pinhead formation and pinhead formation to harvesting and yield components (biological, yield, economic yield, total number of harvest per tray, harvest interval, number of harvesting, test of relationship of fractal temperature and fractal humidity to biological yield and economic yield) are similar with different duration of incubation and growing orientations of fruiting bags. However, in terms of pileus diameter sliced longitudinally is significantly higher that lying position and conventional method. The 4 months old fruiting bag is significantly higher than 2 months old fruiting bags when it comes to diameter of stipe. The length of stipe sliced longitudinally is significantly higher than the other growing orientations. Proximate analysis showed that milky mushroom has 81.36 0.27 moisture, 1.72 0.16 ash, 3.340.36 crude protein, 1.480.15 crude fat, 2.040.22 crude fiber, and 10.06 nitrogen-free extraction (NFE) indicating that milky mushroom is suitable for ages 10 and above even for pregnant and lactating women. The conventional method with 4 months incubation period was noted to have the highest total sale, net income and return of investment among the other treatments. As of growth characteristics, two or four months of incubation and different growing orientation are highly recommended.